Preparation and Standardization of Nosodes Sourced from Klebsiella Pneumoniae, Salmonella Typhi, Neisseria Gonorrhoeae and Candida Albicans Strains - Munshi, Renuka; Talele, Gitanjali; Shah, Rajesh (Homeopathy, 2021)
Background Homeopathic nosodes prepared from organisms and pathological tissues have shown biological effects, encouraging more research. There is a need to develop some new nosodes systematically and to re-make others that were developed over a century ago. In our program of work on nosodes, the bacterial strains Klebsiella pneumoniae (BAA 2146), Salmonella typhi and Neisseria gonorrhoeae (ATCC 43069), and the single-celled fungus Candida albicans (24433, 26790, and 60193) have been identified for preparation.Materials and Methods The systematic and scientific method of preparation of nosodes includes identification, culture, quantification, characterization, preparation, and standardization. Under laminar flow, a suspension of respective bacterial and fungal cells (20 billion cells/mL) was processed as per the Homoeopathic Pharmacopoeia of India (HPI). Culture tests, sterility tests and molecular testing (polymerase chain reaction) were performed to establish the absence of contamination, live organisms and DNA material.Results K. pneumoniae, S. typhi (single, bivalent, or polyvalent), N. gonorrhoeae, and C. albicans nosodes (single and polyvalent) were sourced and prepared from different strains of respective cultures. The nosode preparations were processed by serial dilution and potentization, normally following the HPI guidelines. Molecular test results showed the absence of live organisms or DNA material; culture and sterility test results demonstrated the safety profile of the potentized nosodes.Conclusion K. pneumoniae, S. typhi, N. gonorrhoeae and C. albicans nosodes were successfully prepared. Their therapeutic potential may now be evaluated.
Keywords: Klebsiella pneumonia; Salmonella typhi; Neisseria gonorrhoeae; Candida albicans; nosode; potentization; homeopathy